Enabling farming data traceability in Mexico - González, Daniel; Flores, Samuel; Gardeazábal Monsalve, Andrea (International Food Policy Research Institute, 2022)
CGIAR Research Initiative on Digital Innovation collaborated with CIMMYT and Bluenumber to deploy a pilot project in Mexico to evaluate a scalable data traceability approach that can incentivize farmers' sharing data and sustainable production using open data sharing protocol with the self-sovereign identity (SSI) technology. This progress report from Bluenumber provides an overview of the project activities in 2022.